Anaplastic astrocytoma. (July 2016) - Grimm, Sean A; Chamberlain, Marc C
Anaplastic astrocytoma (AA) is a diffusely infiltrating, malignant, astrocytic, primary brain tumor. AA is currently defined by histology although future classification schemes will include molecular alterations. AA can be separated into subgroups, which share similar molecular profiles, age at diagnosis and median survival, based on 1p/19q co-deletion status and IDH mutation status. AA with co-deletion of chromosomes 1p and 19q and IDH mutation have the best prognosis. AA with IDH mutation and no 1p/19q co-deletion have intermediate prognosis and AA with wild-type IDH have the worst prognosis and share many molecular alterations with glioblastoma. Treatment of noncodeleted AA based on preliminary results from the CATNON clinical trial consists of maximal safe resection followed by radiotherapy with post-radiotherapy temozolomide (TMZ) chemotherapy. The role of concurrent TMZ and whether IDH1 subgroups benefit from TMZ is currently being evaluated in the recently completed randomized, prospective Phase III clinical trial, CATNON.